Manual educacional em saúde ocular para o médico do tráfego - Sleiman, Toufic Mohamad [UNIFESP] (2018)
Objective: This study has as its main objective to elaborate a reference manual for the medical evaluation of the candidates who are willing to obtain the carteira nacional de habilitação (CNH), making it possible to create guidelines in the area of Traffic Medicine. Methods: It was revised pertinent and relevant literature concerning national and international legislation as well as the literature of related eye diseases that interfere with safety and driving. Specific examinations such as visual acuity, visual field, chromatic vision, contrast sensitivity and night vision were also considered in the preparation of the manual. Results: The manual was divided into 13 chapters: general considerations, visual acuity, visual field, chromatic vision, contrast sensitivity, night vision, cataract, glaucoma, diabetic retinopathy, age-related macular degeneration, strabismus, monocular vision and the ametropias, covering the introduction to the Traffic Medicine and related subjects to vehicular direction. Conclusions: This manual intends to serve as literature reference for the traffic examiners by establishing visual function parameters necessary to obtain and/or renew the Motor Vehicle Driver’s License (Brazilian CNH).